Judicial Review of Municipal Legislation on Hazard Games in the Czech Republic - Kohajda, Michael; Moravec, Jiri (Public Governance, Administration and Finances Law Review, 2019)
The aim of the article is to discover fundamental regulating legislative activities of municipalities in the field of hazard games. For several recent years there have been a lot of problematic cases relating to authorisations to carry on hazard games in the Czech towns and villages that have had to be decided by the Ministry of Finance and later by administrative courts and the Constitutional Court. Some of the decisions can be considered fundamental and very relevant for fundamental principles of municipal legislation making. The authors focus on elected court decisions with the aim to evaluate the practise of municipalities in the field.